Pengaruh Permainan Tradisional Gobak Sodor terhadap Peningkatan Motorik Kasar pada Siswa Kelas IV SDN 1 Cipedes - Helmy Febriansyah; Didi Muhtarom; Boby Agustan (Pusat Riset dan Inovasi Nasional, 2024)
This research includes research objectives to evaluate the effect of the traditional game Gobak Sodor on improving gross motor skills. The research method used is a quantitative method with a one group pretest-posttest research design. The research population was class IV students at SDN 1 Cipedes, the sample used was a purposive sampling technique with a sample of 16 class IV students. Data collection techniques were carried out through pre-tests and post-tests regarding students' abilities in terms of running speed. The research instrument used was a running speed test with a distance of 30 meters. Before the posttest, the researcher will provide treatment in the form of practicing the game Gobak Sodor. After the pretest-posttest is carried out, the researcher will carry out data processing to determine the students' running speed after practicing the game Gobak Sodor.